Movement of Microphytobenthos and Sediment Between Mudflats and Salt Marsh During Spring Tides - Redzuan, Nurul S.; Underwood, Graham J. C. (Frontiers in Marine Science, 2020)
The movement of sediment and associated microphytobenthos (MPB) between the upper mudflat and salt marsh in a macrotidal estuary was investigated by comparing the variability of benthic chlorophyll a (Chl. a) and suspended Chl. a during flood and ebb spring tides during the 2015 super moon event. Sampling was carried out for four days in August and September. Flood tide water carried significantly higher amounts of Chl. a from the mudflat transition zone onto the salt marsh compared to the amount of leaving the salt marsh during ebb tides. Suspended solid loads, suspended Chl. a concentrations, and diatom species composition provided evidence that resuspended mudflat sediments containing biofilm material was transferred onto the salt marsh by flood tide. Significant negative correlations between sediment Chl. a concentrations on the upper mudflat transition zone and Chl. a concentrations in flood tide water indicated biostabilisation of sediments by biofilms reducing sediment resuspension. Mean wind speed had a significant positive effect on resuspending Chl. a from the salt marsh sediment surface into the ebb tide (p < 0.001). The amount of Chl. a being resuspended in flood and ebb tidal waters was significantly correlated with MPB biomass on the sediment surface on the mudflat and salt marsh, respectively. Resuspended diatoms over the mudflat during high tide shared a total of 54.3 % similar species with diatoms recorded in flood tidal water over the salt marsh. Diatom taxa characteristic of salt marsh assemblages, and some deposited diatom taxa were resuspended and carried off the salt marsh during ebb tide. Resuspension of Chl. a in both flood and ebb waters was significantly controlled by the tidal range (both significant at p < 0.001). During spring tides, there was a net movement of characteristic MPB mudflat diatom taxa and sediment from the adjacent mudflat to the salt marsh, contributing to the accumulation of material within vegetated marshes during summer months.